Signifikansi Nilai Simbol Budaya Dan Nilai Religi Pada Pemugaran Arsitektur Warisan di Pura Kentel Gumi Kabupaten Klungkung - I Kadek Pranajaya (Jurnal Penelitian Agama Hindu, 2022)
Kentel Gumi Temple is one of the oldest temples in Bali which has its own uniqueness because there are many archaeological objects stored in the temple area. Not many people know about the unique process of Kentel Gumi Temple and the process of restoring the temple compared to other temples in Bali. This research was conducted with a qualitative exploration method to examine the significance of the values ​​of cultural symbols and religious values ​​in the process of restoring the cultural heritage architecture at the Kentel Gumi Temple. In addition, to explore the activities of preserving architectural forms and ritual values. The results of the study found that the restoration of the Kentel Gumi Temple was significant for maintaining the value of cultural symbols and religious values ​​with the discovery of many archaeological objects from the lytic tradition in the form of menhirs, as well as relics from the classical period such as the Pancer Jagat shrine which is the unit that has the greatest cultural significance value. , considering that this building unit is an early milestone in the development of Kentel Gumi temple. The presence of a bronze phallus and stone in the Meru pelinggih overlapping solas, chess advance pelinggih, ancient statues in the form of 4 (four)-faced Lord Brahma made of solid stone, pelinggih gedong statues (queen puseh), and Ganesha statues. While the religious value can be seen from the ritual procession of restoration through spiritual transfer of all buildings through a form of symbol transfer called tapakan pelinggih with a set of upakara daksina, procession of building pralines, determination of layout (nyukat), excavation work (ngaruwak), ngenteg linggih ceremony to Tawur Panyegjeg Jagat level ceremony.